2004
DOI: 10.1176/appi.ajp.161.7.1247
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Social Perception Associated With Lesions of the Prefrontal Cortex

Abstract: These findings of deficits in social perception after damage to the orbitofrontal cortex extend previous clinical and experimental evidence of damage-related impairment in other aspects of social cognition, such as the ability to accurately evaluate emotional facial expressions. In addition, the results suggest that the dorsolateral prefrontal cortex is recruited when inferences about social interactions are made on the basis of nonverbal information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(93 citation statements)
references
References 55 publications
6
80
0
7
Order By: Relevance
“…These regions may represent a functional circuit recruited during social judgements of a more cognitive and less affective nature. Lesions of the dorsolateral prefrontal cortex have been shown to result in impairments in the ability of subjects to use social cues to make interpersonal judgements, supporting a functional role of the dorsolateral prefrontal cortex in some forms of social decision making (Mah et al 2004). Activation of the dorsolateral prefrontal cortex and caudate nucleus may also relate to the overall cognitive load, as the RT data indicate that the intelligence judgement task is more cognitively demanding than the approachability task.…”
Section: Discussionmentioning
confidence: 96%
“…These regions may represent a functional circuit recruited during social judgements of a more cognitive and less affective nature. Lesions of the dorsolateral prefrontal cortex have been shown to result in impairments in the ability of subjects to use social cues to make interpersonal judgements, supporting a functional role of the dorsolateral prefrontal cortex in some forms of social decision making (Mah et al 2004). Activation of the dorsolateral prefrontal cortex and caudate nucleus may also relate to the overall cognitive load, as the RT data indicate that the intelligence judgement task is more cognitively demanding than the approachability task.…”
Section: Discussionmentioning
confidence: 96%
“…Patients were observed to become less respectful of social normality as well as exhibiting impairments of concentration, initiative, spontaneity, and abstract reasoning (Dolan, 2007). More recent studies of patients with discrete prefrontal cortical lesions have also shown impaired behavioural responses to certain hierarchies (Karafin et al, 2004), a deficit in social perception (Mah et al, 2004), defective social decision-making (Eslinger and Damasio, 1985;Barrash et al, 2000) and impaired social reasoning in response to authority and punishment (Anderson et al, 1999 social alliance conditions were also associated with activation of bilateral fusiform gyri and widespread posterior cortical regions including lingual gyrus. The latter finding suggests that a broader network of brain regions, both 'higher' and 'lower', rostral and caudal, is activated in concert when more complex processing is required (e.g., judging hierarchical status elicits more from the network than a more superficial judgment, such as 'who is older?…”
Section: Discussionmentioning
confidence: 99%
“…The anterior cingulate and ventromedial, orbital, and dorsolateral prefrontal cortex are other brain structures that appear to play an important role in other aspects of social cognition, such as the understanding of other's mental statues (i.e., theory of mind) and emotional regulation (Allman, Hakeem, Erwin, Nimchinsky, & Hof, 2001;Amodio & Frith, 2006;S. Anderson, Bechara, Damasio, Tranel, & Damasio, 1999;Bechara, Damasio, & Damasio, 2000;Frith & Frith, 2001;Gallagher & Frith, 2003;Goel, Grafman, Sadato, & Hallett, 1995;Grattan & Eslinger, 1989;Mah, Arnold, & Grafman, 2004;Siegal & Varley, 2002). Figure 2 portrays the various brain regions that have been implicated in social cognition and behavior, and Table 1 summarizes some of the links between those regions and specific socialcognitive and affective processes that have been the focus of research to date.…”
Section: The Emerging Discipline Of Social Cognitive Neurosciencementioning
confidence: 99%